Protection of Refugees Right to Education from a Legal Political Perspective in Indonesia - Sugihardana, Danang; Prasetyowati, Novia Indah; Rindjani, Nisrina Alya (Journal of Law Justice (JLJ), 2025)
Indonesia's strategic position not only provides advantages in trade and economic aspects but also makes the country an important point in global migration flows. Many asylum seekers travel to Indonesia, some as a transit country or settling here, even though Indonesia has not ratified the 1951 Refugee Convention. This research will attempt to analyze, from a legal-political perspective, the protection of refugees' rights to education in Indonesia. Although Indonesia has yet to ratify the 1951 Refugee Convention and the 1967 Protocol, Indonesia as a State Party is bound by various international human rights instruments, including the 1989 Convention on the Rights of the Child, that guarantee the right to education for each child, including refugee children. But in the field of implementation, refugees' educational rights are limited by national policies which are more concerned about security aspects rather than human rights. The Presidential Regulation No. 125/2016 on Management of Refugees from Abroad mentions no discussion related to refugee rights, including the right to education. Purpose of this research is to analyze existing regulations related to the protection of refugees' educational rights and obtain access to challenges in its implementation at the national level. Material and Methods Normative approach, where materials are reviewed from literature with regard to national and international laws and regulations. Discussion The research findings show that access to formal education by refugees in Indonesia is very limited. Most refugees do not have student identification numbers, which makes them non-existent in the national education system. Other obstacles include community anxiety over social and economic impacts caused by their presence. The study, therefore, recommends that policy improvements for inclusivity, coupled with increased collaboration at the level of government, international organizations, and local communities, will ensure that the rights of refugees to education are met in keeping with international standards.